Astudy About Some Physiological Parameters In Smokers - Al-Azzawy, L. H. A.; Al-Qaicy, A. G. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Smoking has been accepted as a risk factor for many chronic diseases, including cardiovascular diseases, respiratory diseases, cancer, ulcers and osteoporosis. Tobacco smoke contains many oxidants and free radicals that can cause damage to lipids, proteins, DNA, carbohydrates and other biomolecules. In vivo, antioxidant nutrients which include vitamin C, selenium (Se), zinc (Zn) and copper (Cu) play a crucial role in defending against oxidant damage. The present study was designed to investigate the influence of cigarette smoking on serum  Zn, Cu ,PCV,W.B.Cs., and BMI. Eighty healthy men (40 smokers and 40 non-smokers) from Baghdad, the capital of Iraq, volunteered to participate in this study.  Two overnight fasting blood samples were collected from all volunteers. Serum concentrations of trace elements were measured by atomic absorption spectrophotometer. The statistical method of t-test and ANOVA was used to identify differences between the cigaretteâ€™s smoker and non-smoker group. Mean body mass index (BMI) was different for the smoker and non-smoker group. Mean of PCV for smoker was significantly (p